Penilaian kualitas visual dan aspek sapta pesona pada lanskap Bali Zoo di Desa Pakraman Singapadu, Gianyar - Kurniawan, I Kadek Ari; Sugianthara, Anak Agung Gede; Astiningsih, Anak Agung Made (Jurnal Arsitektur Lansekap; Vol.5, No.1, April 2019DO - 10.24843/JAL.2019.v05.i01.p02, 2019)
Assessment of the Visual Quality and Sapta Pesona Aspect on Bali Zoo Landscape in Singapadu Traditional Village, Gianyar. Bali Zoo is one of the artificial landscapes in the form of a zoo with educational, conservation, and tourism functions. This zoo has a vision to make Bali Zoo as an international zoo standards. Some efforts that can be done to realize the vision is by improving the aesthetic quality and aspects of sapta pesona. The assessment of visuals quality and aspects of sapta pesona in Bali Zoo aims to evaluate both visuals quality and sapta pesona aspect in the Bali Zoo landscape. Methods used in this research was field survey with observation, questionnaire, interview, and literature review techniques. The result was a description of the assessment of visuals quality and aspects of sapta pesona on Bali Zoo landscape, therewith recommendation that can be given in the form of recommendation might improve the visuals quality and aspects of sapta pesona on Bali Zoo landscape. It is concluded that the visuals quality and aspects of sapta pesona on Bali Zoo landscape were quite good and it can improve the aesthetic visuals quality of Bali Zoo landscape by improving the quality of landscape elements, whereas improving the aspects of sapta pesona from the elements of security, discipline, hygiene, beauty, coolness, friendliness, memory. These recommendation was suitable to apply by the manager, visitors and students.